O narrador e o efeito de horror em narrativas da literatura brasileira - Máximo, Ana Beatriz Cruz (2021)
This research proposes to analyze the ways in which the narrator’s positioning and his speech, allied to the time and space components, determine the construction of the atmosphere and emotion of fear in horror short stories in Brazilian Literature, published between late 19th century and early 20th century. For that, we selected as corpus of this research three short stories – “Demônios” (1891), from Aluísio de Azevedo, “O bebê de tarlatana rosa” (1910), from João do Rio and “Noturno nº 13” (1920), from Gastão Cruls –our main criterion was the fact that they use different tools to achieve the horror effect, from the position of the narrators centered on the 1st. person, however, shifting between being in the diegesis as characters (autodiegetic) or on the margin of the story (homodiegetic), as spectral presences, to the use of metafiction, carnival or ghost masking as triggering cores of horror. The guiding inquiry of this research questions if the narrator’s position is primordial to construct the effect of fear in horror narratives and the general hypothesis is that this position, allied to the construction of time and space, can influence the construction of an atmosphere of fear. Organized in three chapters, this dissertation begins with a presentation of the main conceptions of this literary modality, based on the studies of Howard Philips Lovecraft, Edgar Allan Poe, Tzvetan Todorov, Xavier Aldana Reys, Stephen King and Edmund Burke. In the second chapter, we go through the narrator’s theory, which was already seem by the theoretical investigations of Wayne Booth, Maria Lucia Dal Farra, Gérard Genette and Carlos Reis. In the third chapter, we analyzed the short stories selected through the theoretical foundations that supported this research. We concluded, through the corpus’ analysis, that our hypothesis is valid because it shows how the narrator’s figure and his position in the narrative, in the in-and-out game, is capable to produce a fine atmosphere so the horror effect in the reader’s mind happens